'A War Imagined': Postcards and the Maintenance of Long-Distance Relationships during the Great War. (April 2021) - Mayhew, Alex
This article explores the role of postcards in the maintenance of relationships between combatants and civilians during the First World War. By drawing on untapped archival material found during wider research into the morale of English infantrymen, it concentrates on the multiple uses of this medium in correspondence between the Western and Home Fronts. Following the 'cultural turn' in military history it has become increasingly apparent that the gulf between those fighting and those left at home was much narrower than previously assumed. This analysis charts the variety of ways in which postcards helped to bridge this divide.